Sains dan Kesucian: Menjembatani Ilah-Ilah dalam Citra Manusia Sendiri - Hutapea, Jusuf (Indonesian Journal of Religious, 2024)
This article discusses the relationship between science and spirituality, aiming to explore whether they can serve as a bridge in the search for truth or instead act as a barrier. The background of this study focuses on the historical tension that often arises between science, which prioritizes empirical evidence, and spirituality, which is more subjective and belief-based. The research adopts a qualitative approach using content analysis, reviewing various relevant literatures to find common ground between these two fields. The findings suggest that, despite the existing tension, science and spirituality have the potential to complement each other in understanding the universe, life, and the meaning of existence. The main contribution of this article is offering a more inclusive perspective on the interaction between science and spirituality, which could foster more constructive dialogue between the two. Artikel ini membahas hubungan antara sains dan spiritualitas, dengan tujuan untuk menggali apakah keduanya dapat menjadi jembatan dalam pencarian kebenaran atau justru berfungsi sebagai penghalang. Latar belakang penelitian ini berfokus pada ketegangan historis yang sering terjadi antara sains yang mengutamakan bukti empiris dan spiritualitas yang lebih bersifat subjektif dan keyakinan. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis konten, yang mengkaji berbagai literatur terkait untuk menemukan titik temu antara kedua bidang ini. Hasil penelitian menunjukkan bahwa meskipun terdapat ketegangan, sains dan spiritualitas memiliki potensi untuk saling melengkapi dalam memahami alam semesta, kehidupan, dan makna eksistensi. Kontribusi utama artikel ini adalah menawarkan perspektif yang lebih inklusif mengenai interaksi antara sains dan spiritualitas, yang dapat membuka ruang untuk dialog yang lebih konstruktif antara keduanya.